PENGARUH GAYA MENGAJAR KOMANDO DAN MOTOR ABILITY RENDAH TERHADAP HASIL BELAJAR TENDANGAN DOLYO CHAGI TAEKWONDO - tri juniar, dicky (Journal of Sport Science and Education, 2017)
The purpose of this study is to obtain information about the influence of command teaching style and low motor ability to the results dolyo chagi kick Taekwondo students PJKR Siliwangi University Tasikmalaya City. The method used in this research is experimental method. The sampling used by the author with a simple random assignment (random assignment). The result of his research is the style of command teaching gives a significant influence for students with low ability motor to the learning result kick dolyo chagi (q0 = 4,63 <qt = 3,63). It is expected that all lecturers and teachers in providing sports learning to learners whose motion skills are low, especially learning taekwondo better using the command teaching style.